Physiological and Biochemical Characteristics, of Yeast 3SJ and Its Inhibitory Effect on Postharvest Diseases of Apple - Gong, Wenfeng; Yue, Haimei; Wang, Mu; Ma, Qing (Plant Diseases and Pests(植物病虫害研究：英文版), 2012)
The physiological and biochemical characteristics of the yeast 3SJ with resistance against three species of postharvest diseases were identified in the pa- per, and the inhibitory effects of the yeast 3SJ on Penicillium expansum, Botrytis cinerea and Colletotrichum gloeosporioides during storage period was preliminarily studied. The control effects of the yeast on postharvest diseases caused by P. expansum, B. cinerea and C. gloeosporioides were measured in vivo and in vitro condi- tions. The results showed that the yeast had best control effect against P. expansum and B. cinerea at 20 ~C ; followed by the control effect against C. gloeospori- oides. Inoculation of spore suspension of yeast in apple wound could effectively inhibit rot of apple, while supematant filtrate and sterilized liquid could not inhibit rot of apple. This simultaneously indicated that the action mode of the yeast mainly was nutrition competition. The yeast was conducted traditional classification and identification based on physiological and biochemical characteristics of the yeast, and preliminarily identified to be Kloechera spp. The yeast could survive for at least one month in apple wound at 4 ~C low temperature conditions, with increased amounts. The tolerance to low temperature laid the foundation for application of yeast in low-temperature refrigeration of fruits.